2013
DOI: 10.1155/2013/756789
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and IgE-Binding of Glycosylated Codfish Parvalbumin

Abstract: Food-processing conditions may alter the allergenicity of food proteins by different means. In this study, the effect of the glycosylation as a result of thermal treatment on the digestibility and IgE-binding of codfish parvalbumin is investigated. Native and glycosylated parvalbumins were digested with pepsin at various conditions relevant for the gastrointestinal tract. Intact proteins and peptides were analysed for apparent molecular weight and IgE-binding. Glycosylation did not substantially affect the dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…These results were confirmed by dot-blot assay, showing that the intensity of spots became weak in 11 patients tested. Several studies are consistent with our findings which indicate the reduction of the allergenicity of fish parvalbumin by enzymatic digestion processing (Cai et al, 2010;De Jongh et al, 2013;Untersmayr et al, 2003). Those results suggest that the CPP epitopes recognized by human IgE are partially conformational, while remaining binding of pepsin digested CPP to human IgE indicated that a large part of epitopes involved were sequential.…”
Section: Discussionsupporting
confidence: 92%
“…These results were confirmed by dot-blot assay, showing that the intensity of spots became weak in 11 patients tested. Several studies are consistent with our findings which indicate the reduction of the allergenicity of fish parvalbumin by enzymatic digestion processing (Cai et al, 2010;De Jongh et al, 2013;Untersmayr et al, 2003). Those results suggest that the CPP epitopes recognized by human IgE are partially conformational, while remaining binding of pepsin digested CPP to human IgE indicated that a large part of epitopes involved were sequential.…”
Section: Discussionsupporting
confidence: 92%
“…The spectrum of native pea protein showed two minima around 222 and 208 nm and a zero crossing at 204 nm, indicative of a secondary structure that is highly predominated by α-helical and some β-sheet contributions. 35 Upon heating of pea protein at pH 2.0, a shift at the zero crossing to 197 nm was observed, illustrating a considerable loss of β-sheet strands. Substantial amounts (about 20%) of β-sheet were, however, still present in pea protein heated at pH 2.0 when the far-UV CD spectra were analyzed by the method previously described.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…A protein ladder, Precision Plus Protein Dual Xtra standards (Biorad, Hercules, CA, USA), was used to estimate molecular weight. Immunoblotting was performed as described elsewhere using rabbit anti‐shrimp TM IgG (Indoor Biotechnologies, Charlottesville, VA, USA), [ 15 ] plasma, or sera each diluted in 2.5% non‐fat dry milk in PBS with tween (0.05% Tween 20, 1x PBS, pH 7.4). Rabbit anti‐shrimp TM IgG was diluted 1:4000 followed by 1:4000 goat anti‐rabbit IgG peroxidase conjugated (Thermo Scientific, Waltham, WA, USA) and sera or plasma were diluted 1:10 followed by 1:1000 mouse anti‐human IgE peroxidase conjugated (Southern Biotech, Birmingham, AL, USA).…”
Section: Methodsmentioning
confidence: 99%